The Role of Stakeholders in Increasing the Quality of Lake and River Traffic Service Unit in Jatiluhur Dam - Iqbal Syaefulloh; Gina Indah Permata Nastia; Yudhistira Anugerah Pratama (Lingkar Studi Komunikasi (LISKI), 2023)
West Java is one of the regions in Indonesia which has a fairly large water area, so the existence of water transportation services, also known as lake and river transportation traffic service unit, is very much needed to help people move around, namely in the Saguling Dam area. which is located in West Bandung Regency, Cirata Dam which is located in Cianjur Regency, and Jatiluhur Dam which is located in Purwakarta Regency. Jatiluhur is an area of lake and river traffic service unit that still needs to improve the quality of service when compared to the other three dams in West Java. In fact, the existence of water transportation in Jatiluhur is one of the livelihoods that can help empower local communities in the economic sector. Therefore, the role of various stakeholders is needed to improve the quality of lake and river traffic service at the Jatiluhur Dam. This research aims to describe the role of stakeholders in improving the quality of services of lake and river traffic service unit at Jatiluhur Dam. This research used a qualitative descriptive method, in which the selected informants came from 82 stakeholders who were involved, either directly or indirectly, in efforts to improve the quality of services of lake and river traffic service unit at Jatiluhur Dam. The results of the research indicated that stakeholders have various roles in improving the quality of services of lake and river traffic service unit at Jatiluhur Dam. Keywords: Lake and River Traffic Service Unit, Local Community, Empowerment, Economy, Role of Stakeholders